The Influence of Social Media on the Knowledge of Youth about People with HIV and AIDS - Nani Kusniati; Dede Sri Mulyana (STIKep PPNI Jawa Barat, 2022)
Aims: HIV/AIDS has several negative impacts, namely social impacts, human resource development, demographics, health sector, education sector, and religious aspects. One of the social impacts of HIV/AIDS is that 49.7% stigma occurs between the community and people with HIV/AIDS. Methods: This study uses a Chi-Square research design, namely research that determines the time of measurement/observation of independent and dependent variable data only once at a time Results: The results of the Kai Square (Chi-Square) statistical test at = 0.05 obtained a p-value of <0.001 (p≤ 0.05), which means that there is a statistically significant relationship between social media and the knowledge of active students in class IX about People with HIV. / AIDS (PLWHA). Conclusion: The suggestion in this study is that schools can cooperate with higher health education institutions to improve preventive actions including primary prevention by various ways of providing knowledge about People with HIV/AIDS.